Measuring creative economy in Indonesia: Issues and challenges in data collection - Eni Lestariningsih; Karmila Maharani; Titi Kanti Lestari (Asia-Pacific Sustainable Development Journal, 2019)
Although creative economy is emerging as an area to be evaluated, establishing a benchmark against which it can be measured is still problematic due to a range of definitional problems, both conceptual and practical. In recent years, many agencies and governments have invested significant effort into collecting data on creative economy, but in many countries, including Indonesia, measuring creative economy remains a challenge. Data collection on creative economy has been conducted twice in Indonesia, initially through surveys undertaken in 2016 and then in a compilation of the 2016 Economic Census. The data collection used a common classification system to identify the five-digit Indonesia Standard Industrial Classification (KBLI) regarded as creative economy. Out of a total of 1,573 five-digit KBLI codes, there are 223 which are identified as creative economy activities. However, this approach remains unstandardized in terms of concept definitions, data collection procedures, methods of analysis and common classification systems. This paper highlights the numerous limitations in current creative economy measurement in Indonesia, identifying issues and challenges in data collection and creative economy measurement processes that are needed to support the Sustainable Development Goals.